2016
DOI: 10.1161/circulationaha.115.018830
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in the Use of Cardiac Resynchronization Therapy With or Without Implantable Cardioverter-Defibrillator

Abstract: Background Candidates for cardiac resynchronization therapy (CRT) receive either a biventricular pacemaker (CRT-P) or a biventricular pacemaker with an implantable-cardioverter defibrillator (ICD; CRT-D). Optimal device selection remains challenging as the benefit of ICD therapy may not be uniform, particularly in patients at competing risk of non-sudden death. Methods and Results In this serial cross-sectional study using the National Inpatient Sample database, we identified 311,086 admissions associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 51 publications
(57 reference statements)
4
38
1
Order By: Relevance
“…Among defibrillators, the proportion of single‐chamber/dual‐chamber/resynchronization devices was 21%/37%/42%, respectively. Collectively, these characteristics are similar to those noted in national databases inclusive of all manufacturers' devices …”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Among defibrillators, the proportion of single‐chamber/dual‐chamber/resynchronization devices was 21%/37%/42%, respectively. Collectively, these characteristics are similar to those noted in national databases inclusive of all manufacturers' devices …”
Section: Resultssupporting
confidence: 73%
“…The NCDR does not register these devices. In the National Implant Sample, CRT‐P accounted for 14% of implanted resynchronization devices in 2009, with 58% male proportion and age 75 years (ie, demographics identical to our cohort) . However, this registry lacks postimplant follow‐up data.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies of geographic variation in treatment and spending have focused on traditional fee‐for‐service Medicare populations, but the Institute of Medicine has called for more understanding of variation in commercially insured populations, including Medicare Advantage 16. One recent study used the National Inpatient Sample to characterize CRT‐D versus CRT‐P and found significant variation among hospitals 17. We build on these efforts, examining both inpatient and outpatient procedures.…”
mentioning
confidence: 99%
“…16 One recent study used the National Inpatient Sample to characterize CRT-D versus CRT-P and found significant variation among hospitals. 17 We build on these efforts, examining both inpatient and outpatient procedures. Thus, we sought to evaluate patients treated with implantable cardiac devices as measured in a large national commercial claims database, focusing on the overall, temporal, and geographic variation in the United States between 2008 and 2013.…”
mentioning
confidence: 99%